Relationship Between Cigarette Smoke Exposure and Laryngeal Histopathology in Rattus novergicus Rats - Nasution, Erizal Salam Putra; Herwanto, H. R. Yusa; Zahara, Devira; Aliandri, Aliandri; Lubis, Yuliani M.; Ashar, Taufik; Chrestella, Jessy (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Smoking can cause health problems for both active and passive smokers because the toxic substances contained in it cause health problems, especially in the larynx, one of which is laryngeal cancer. Animal studies have shown histopathological changes in mice exposed to cigarette smoke, including increased immune cells and focal inflammation in these mice. The study aims to determine the relationship between cigarette smoke and the number of inflammatory cells, edema, hyperplasia, and dysplasia after exposure to cigarette smoke for 120 minutes in histopathological sampling at observations of 0, 10, 20, 30 and 40 days. This study used a true experimental design model with a post-test only group laboratory experimental design. The results of the study found a significant difference in the number of lymphocytes before and after exposure to cigarette smoke with p = 0.043. There was no significant change in the number of macrophages with p = 0.406 and eosinophils with p = 0.119. There were no histopathological changes, namely edema (p = 0.06), dysplasia (p = 0.126) and hyperplasia (p = 0.960). In conclusion, there is a relationship between cigarette smoke exposure and laryngeal histopathology in Rattus novergicus Rats.